2000
DOI: 10.1055/s-2000-11805
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Charakteristika von Patienten mit tardiven Dyskinesien

Abstract: 97 out of 233 patients (= 41.6%) displayed persistent tardive dyskinesia. In univariate analysis, significant associations were found between tardive dyskinesia and the following independent variables (higher values means greater risk): Age (p = 0.0001), years from onset of the disorder (p = 0.001), total length of stay in hospital (p = 0.001), PANSS (single scales and sum score) (p = 0.0001), total amount of neuroleptics expressed as CPZ equivalents (p = 0.004). Logistic regression analysis showed that only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
2
1
1
Order By: Relevance
“…Second, patients with TD had significantly higher scores on the general PANSS subscales, which suggests that somatic, anxiety, mood and other psychopathologic symptoms were higher in TD patients than in non-TD patients. This differs from the previous studies that found that only PANSS negative symptoms were associated with TD [32] and that the presence of TD was not correlated with higher PANSS scores [33] . Our study is subject to several limitations.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, patients with TD had significantly higher scores on the general PANSS subscales, which suggests that somatic, anxiety, mood and other psychopathologic symptoms were higher in TD patients than in non-TD patients. This differs from the previous studies that found that only PANSS negative symptoms were associated with TD [32] and that the presence of TD was not correlated with higher PANSS scores [33] . Our study is subject to several limitations.…”
Section: Discussioncontrasting
confidence: 99%
“…All subjects underwent detailed interrogation of their drug history. Assessment of lifetime antipsychotic dose was done retrospectively based on medical records and patients' report in a standardized manner as described elsewhere [23]. To sum up the dosage level of different drugs, lifetime antipsychotic dose was converted into chlorpromazine equivalents (CPZ).…”
Section: Methodsmentioning
confidence: 99%
“…Age, regardless of the duration of treatment, is an important risk factor for TD, as TD is five to six times more prevalent in the elder (445 years) than in younger patients. 3,4 Even though newer (or 'atypical') antipsychotics have a lower or perhaps negligible risk to induce TD, 5 classical (or typical) antipsychotics are, however, currently still prescribed for many reasons: Typical antipsychotics are less expensive than atypical antipsychotics, which may globally be one leading reason. Moreover, some patients do not respond or tolerate treatment with atypical antipsychotics that may cause side effects as weight gain or diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%